Barriers to Antenatal Care Utilization in Indonesia (Medico Legal Update, 2021)
MMR data in Indonesia fluctuates according to the data source used. Based on Indonesia Demographicand Health Survey data, MMR in Indonesia in 1990 was 390 per 100,000 live births, in 2004/2007 it was228/100,000 live births, then increased sharply in 2008-2012 by 359/100,000 live births. Whereas based onthe 2015 SUPA data, MMR in Indonesia decreased by 305 per 100,000 per live birth. This study aims toanalyze the barrier to ?4 ANC visits during pregnancy. The analysis uses the 2017 Indonesian Demographicand Health Survey data. Stratification and multistage random sampling method get 15,351 respondents.Barrier determination was done using Binary Logistic Regression. The barriers consisted of the followingvariables: young age, low education, high parity, poverty, not having health insurance, not being able to read,not being exposed to the media, never using the internet, not knowing the danger signs of pregnancy, andbelief in traditional birth attendants